2017
DOI: 10.1111/jog.13515
|View full text |Cite
|
Sign up to set email alerts
|

Annual Report of the Perinatology Committee, Japan Society of Obstetrics and Gynecology, 2016: Overall report on a comprehensive retrospective study of obstetric management of preterm labor and preterm premature rupture of the membranes

Abstract: We conducted a questionnaire survey on the current obstetric management of preterm labor (PL) and preterm premature rupture of the membranes (pPROM). The questionnaire covered approximately a third of all preterm deliveries and nearly half of the preterm deliveries before 32 gestational weeks. The diagnostic criterion for PL was either painful uterine contractions or cervical dilatation. Tocolytic agents were primarily used as long-term maintenance therapy. Intrauterine infection was clinically diagnosed at mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The long‐term maintenance therapy with tocolytic agents has been shown ineffective to prevent preterm delivery by the recent meta‐analyses 12–14 . However, in some countries such as Japan, an acute tocolytic therapy is adopted only in 20% of 45 university hospitals and the remaining 80% use the maintenance therapy followed by the acute tocolysis, 15 which is advocated as one of the treatment choices by the guidelines 1 . Under these circumstances, we found that the prenatal exposure to maintenance magnesium sulfate treatment works protectively, while maintenance B2a treatment and combination treatment has no beneficial impact on the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term maintenance therapy with tocolytic agents has been shown ineffective to prevent preterm delivery by the recent meta‐analyses 12–14 . However, in some countries such as Japan, an acute tocolytic therapy is adopted only in 20% of 45 university hospitals and the remaining 80% use the maintenance therapy followed by the acute tocolysis, 15 which is advocated as one of the treatment choices by the guidelines 1 . Under these circumstances, we found that the prenatal exposure to maintenance magnesium sulfate treatment works protectively, while maintenance B2a treatment and combination treatment has no beneficial impact on the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, commonly used antibiotics, especially cephalosporins, have been largely overlooked in RCTs. A 2018 survey in Japan showed that second-generation cephalosporins and penicillins were the most commonly used antibiotics 76 and, while cephalosporins have been studied in non-randomized trials 77,78 , there is only one small randomized trial in which cephalosporin alone was compared to its combination with erythromycin or clarithromycin 51 . Third, there are antibiotic regimens that have shown promising results in non-randomized trials 79 , but their effectiveness has not been confirmed in RCTs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…They include β2-adrenergic receptor agonists, oxytocin antagonists, calcium channel blockers, non-steroidal anti-inflammatory drugs, and magnesium sulfate [7,8]. Among them, ritodrine, a β2-adrenergic receptor agonist, is among the most commonly prescribed tocolytic agents, particularly in Asia and Europe [9,10]. However, due to safety issues, ritodrine has been withdrawn from the market in several Pharmaceutics 2022, 14, 1220 2 of 9 countries, including the United States [11].…”
Section: Introductionmentioning
confidence: 99%